Preciso de ajuda..
![( \frac{x}{3} + 1)^{3} ( \frac{x}{3} + 1)^{3}](https://tex.z-dn.net/?f=%28+%5Cfrac%7Bx%7D%7B3%7D++%2B+1%29%5E%7B3%7D+)
URGENTE.....
Soluções para a tarefa
Respondido por
1
(x/3 + 1)³
(a + b)³ = a³ + 3a²b + 3ab² + b³
Então,
(x/3 + 1)³ = (x/3)³ + 3.(x/3)².1 + 3.(x/3).1² + 1³
= x³/27 + 3x²/9 + x + 1
= x³/27 + x²/3 + x + 1
(a + b)³ = a³ + 3a²b + 3ab² + b³
Então,
(x/3 + 1)³ = (x/3)³ + 3.(x/3)².1 + 3.(x/3).1² + 1³
= x³/27 + 3x²/9 + x + 1
= x³/27 + x²/3 + x + 1
MicheleHester:
muito Obrigada! ajudou demais.. pela 2 vez. rs
Perguntas interessantes
História,
11 meses atrás
Geografia,
11 meses atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás